2010
DOI: 10.1097/gco.0b013e328337238d
|View full text |Cite
|
Sign up to set email alerts
|

The active management of intrahepatic cholestasis of pregnancy

Abstract: The current literature encourages the induction of labor between 37-38 weeks' gestation in order to reduce the incidence of stillbirth in women with intrahepatic cholestasis of pregnancy. The most widely used medication for both the treatment of maternal pruritus and the elevations in maternal liver enzymes associated with cholestasis of pregnancy is 2-5 ursodeoxycholic acid. Neither mode of practice has been subjected to randomized clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 26 publications
0
55
0
1
Order By: Relevance
“…ICP is classically associated with an increase in adverse perinatal outcomes [17]; intrauterine fetal death (IUFD) is the most devastating of these as the disease frequently occurs in late gestation. The only strategy that has been shown to reduce perinatal mortality associated with ICP is active management of this disease, including elective induction of labor at approximately 37-38 weeks of gestation and the active identification of meconium in the amniotic fluid followed by immediate pregnancy termination if it is found [18,19]. The etiology of IUFD remains unknown; however, it might be associated with a sudden event, because studies have failed to show an association with chronic hypoxia [7].…”
Section: Discussionmentioning
confidence: 99%
“…ICP is classically associated with an increase in adverse perinatal outcomes [17]; intrauterine fetal death (IUFD) is the most devastating of these as the disease frequently occurs in late gestation. The only strategy that has been shown to reduce perinatal mortality associated with ICP is active management of this disease, including elective induction of labor at approximately 37-38 weeks of gestation and the active identification of meconium in the amniotic fluid followed by immediate pregnancy termination if it is found [18,19]. The etiology of IUFD remains unknown; however, it might be associated with a sudden event, because studies have failed to show an association with chronic hypoxia [7].…”
Section: Discussionmentioning
confidence: 99%
“…In our clinic, the diagnosis of ICP was based on the clinical features and biochemical evidence of liver dysfunction in the absence of skin pathology (9,10). Clinical features were characterized as pruritus without a rash.…”
Section: Methodsmentioning
confidence: 99%
“…Clancy et al (2007) showed that hypoxia is thought to contribute to differentiation of human fetal cardiac fibroblasts into myofibroblasts in vitro (Clancy et al, 2007). It has also been postulated that fetal death in ICP may be mediated by bile acid induced vasoconstriction of placental vessels leading to acute hypoxia in these fetuses (Mays, 2010;Sepúlveda et al, 1991). A study by Miragoli et al (2011a) showed that myofibroblasts transiently appear in human fetal ventricular tissue during the second and third trimesters of gestation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%